A Doppler-modulation based veto to discard false continuous gravitational-wave candidates. (19th October 2020) - Intini, G; Leaci, P; Astone, P; Antonio, S D'; Frasca, S; La Rosa, I; Miller, A; Palomba, C; Piccinni, O
Abstract: In this paper we present a chain-of-vetoes algorithm designed to filter out false-positive continuous gravitational-wave candidates returned by all sky searches, such as the frequencyHough pipeline [1 ]. The underlying idea is to use the correlation among candidates (produced by the Earth Doppler effect) in the Hough map to discriminate candidates caused by noise from real continuous-wave signals. Indeed, in presence of a signal, a wrong Doppler correction (due to a mismatch in the sky) can create a candidate with high detection statistic and a small error in estimated frequency and frequency time derivative (s). The current veto scheme allows us to discard 60% of the candidates (with respect to the standard method in [1 ]) as not belonging to a continuous-wave signal, thus reducing the false alarm probability, as well as the computational cost needed to follow up interesting candidates.